57‐3: Folded Pixel Circuit Design in Grain‐Boundary Free (100) Oriented LTPS Stripes Fabricated by Selective CW‐laser Lateral Crystallization. Issue 1 (30th May 2018) - Sasaki, Nobuo; Arif, Muhammad; Uraoka, Yukiharu
Abstract : Effects of scan conditions on grain‐boundary‐free (100) oriented LTPS films by the CW laser lateral crystallization were investigated. Overlapped scans generated grain‐boundaries at the scan regions. A new selective one‐time scan was proposed for high precision mobile OLED panels, where LTPS circuits of neighboring pixels were folded along the scan.